Analysis of Grounding Resistance Performance for Various Bio Fillers Medium Effect - Abdul Malek, Abdul Munzir Hakim; Mohd Jamail, Nor Akmal; Kamarudin, Qamarul Ezani (Evolution in Electrical and Electronic Engineering, 2024)
Electrical grounding, crucially known as earthing, safeguards against electric shocks by redirecting current during short circuits. This study investigates enhancing grounding systems economically using bio-fillers in peat soil to mitigate high soil resistivity. The research aims to improve grounding efficiency by incorporating bio-based materials such as seashells and banana peels. Four configurations—standard copper with peat soil, with banana peel, with seashell, and with a combination of peat soil, seashell, and banana peel—were tested over 30 days to measure grounding resistance. Results reveal that standard copper with peat soil alone demonstrated the most efficient performance with the lowest and most stable resistance (7.5 to 8.4 ohms). The combination of peat soil, seashells, and banana peels showed intermediate resistance (7.7 to 8.8 ohms), while adding banana peels slightly increased resistance (8.5 to 9 ohms). In conclusion, peat soil emerges as the optimal grounding medium due to its effectiveness in achieving low and consistent resistance values.